Influence of ultrasonic vibration on percussion drilling performance for millisecond pulsed Nd:YAG laser. (August 2018) - Wang, Houxiao; Zhu, Sukai; Xu, Guoxiang; Zhou, Wei; Li, Lin; Zhang, Dao Hua; Ren, Naifei; Xia, Kaibo; Shi, Chunhui
Highlights: Ultrasonic vibration was incorporated into millisecond pulsed laser drilling process. Ultrasonic vibration enhanced the laser drilling efficiency. Ultrasonic assistance reduced hole taper and hole wall surface roughness. Ultrasonic vibration improved the microhole morphology/geometry. Ultrasonic vibration made grains finer and improved hardness of heat affected zone. Abstract: The ultrasonic vibration-assisted laser drilling is a recently emerging/growing new technique, especially in laser drilling. Differently from the previous work reported, this paper proposed to use the ultrasonic vibration (25 kHz) for assisting the millisecond pulsed Nd:YAG laser percussion drilling process to improve the drilling performance. Through comparing the drilled microholes without/using ultrasonic assistance, the influence of ultrasonic vibration on the drilled blind hole morphology/geometry, the hole wall surface roughness, the recast layer microstructure, and the hardness distribution of the heat affected zone for the drilled microhole was analyzed by altering laser pulse energy and/or laser pulse number. It was shown that the ultrasonic vibration incorporated into the laser drilling process might enhance the drilling efficiency in terms of the increase of hole depth and width. However, the drilled hole taper might be decreased via using ultrasonic assistance. Moreover, the ultrasonic vibration might clean the inner hole wall surface, and the microhole morphology/geometry could be improved through using ultrasonic assistance, resulting in a relatively clean and better-profiled hole wall with less defects and smaller taper due to the contribution of ultrasonic assistance. In addition, it was indicated that ultrasonic vibration might also improve the microhole heat affected zone hardness and reduce the inner hole wall surface roughness.